Enabling symptom self-management via use of an electronic patient-reported outcomes (ePRO) system to increase self-efficacy of patients with cancer receiving active chemotherapy treatment - Grigorios Kotronoulas; Eileen Furlong; Jo Armes; Christine Miaskowski; Elisabeth Patiraki; Kathi Apostolidis (Frontiers Media S.A., 2015)
Background: In recent years, the shift in cancer services from traditional tertiary care to care delivered within communities has increased the need for patients to engage in self-care activities in order to prevent or reduce the severity of numerous and complex-side effects (McCorkle et al., 2011) and make important health decisions when at home in the absence of clinicians (Butow et al., 2012). The actual degree of engagement in self-management may be dependent on patients' perceived competence or self-efficacy to perform such activities (Fenlon et al., 2015). Self-efficacy has been defined as "a person's belief to execute courses of action required to deal with a prospective situation" (Bandura, 1977, 2001). One's beliefs in their capability to successfully manage tasks and consequently influence situations that impact their lives constitutes a central part of human agency, and can be influenced by performance accomplishments (Bandura, 1989, 2001). Whilst self-efficacy can enable engagement in self-management, actual participation in self-management activities can further increase one's perceived ability to undertake such activities; it is thus obvious that a bi-directional association between self-management and self-efficacy exists. Supporting a shift in clinical practice with innovative technological systems affords a solution to the increasing demands placed on acute care by enabling the delivery of care in the home and community setting (Basch et al., 2011; Carpenter et al., 2008). Such remote monitoring systems facilitate the provision of clear lines of real-time communication between patients and their health care providers (Basch et al., 2011), and can deliver organised self-management advice tailored to the individual's clinical characteristics and severity/distress of symptoms of anti-cancer treatment. Aim(s): Funded by the European Union (FP7 programme), a multi-centre European project (the eSMART study) has been designed to investigate the effects of an electronic patient-reported outcomes (ePRO) system, the Advanced Symptom Management System (ASyMS), on patient outcomes including improvement in self-efficacy, symptom management, supportive care needs, psychological status, work presenteeism, and well-being; health system costs; and the current clinical practice. The primary aim of eSMART is to evaluate the short and long term impact of the ASyMS technology on patient reported outcomes in people with breast cancer, colorectal cancer or haematological malignancies receiving first-line chemotherapy. In addition, eSMART will evaluate the cost-benefit of remote patient-monitoring and changes in clinical practice as a result of the application of the ASyMS intervention in different European healthcare settings. The study is currently recruiting patients, thus no data will be available for presentation. This presentation will nonetheless aim to present and discuss the hypothesis that provision of symptom self-management advice may be an important mechanism to improve patient self-efficacy, which may establish a self-sustained cycle where self-care advice provision enables patient self-efficacy and this in turn further increases patient involvement in self-management that can ultimately lead to improved patient outcomes. Method(s)/Results: The current study has been informed by the Medical Research Council Complex Interventions Framework (Anderson, 2008; Craig and Petticrew, 2012; Mackenzie et al., 2010), and the Holistic Framework to improve the Uptake and Impact of e-Health Technologies (van Gemert-Pijnen et al., 2011). The eSMART programme of work comprises two parts that will take place over a period of five years. The first part consists of preparatory work to refine the ASyMS intervention for use in a multi-national context, and concludes with a feasibility testing period to establish the technological readiness of the system prior to its use in the second part. The second part will employ a repeated-measures, parallel-group, stratified randomised controlled trial methodology to demonstrate the effects of the ASyMS intervention in supporting patients who receive chemotherapy treatment through individualised symptom management. The second part will test the short- (i.e. during the treatment phase) and long-term effects (i.e. at one-year follow-up) of the ASyMS intervention versus standard care across the participating countries (Austria, Greece, Ireland, Norway and the UK). The ASyMS intervention comprises use of a mobile phone (i.e. ASyMS patient handset) and a tympanic thermometer. The patient handset will enable participants on the intervention group to enter symptom/temperature data on a dedicated, electronic symptom questionnaire daily and whenever they feel unwell. Upon successful submission of their data, patients will immediately receive automated, evidence-based self-care advice based on their symptom reports. Patients will also have access to a self-care library, symptom graphs (detailing trends in individual symptoms experienced) and contact numbers of care teams and patient support organisations in their country, available within the ASyMS patient handset. Via dedicated tablet PCs, all participants will complete an electronic version of the Communication and Attitudinal Self-Efficacy scale for cancer (CASE-Cancer) (Wolf et al., 2005) at baseline; after each CTx; and 3, 6, 9 and 12 months post-chemotherapy treatment. The CASE-Cancer is a validated, 12-item measure that yields scores on three factors: understanding and participating in care, maintaining a positive attitude, and seeking and obtaining information. In accordance with latest recommendations for pragmatic research in healthcare (Oakley et al., 2006; Treweek and Zwarenstein, 2009), the longitudinal nature of the trial will aid to establish sustainability of intervention effects and further stress its benefits when compared to standard care. Conclusions: This anticipatory model of care supports symptom management within the patient's home, where the early toxicities of chemotherapy can be managed, utilising self-care and local community services. This model is also expected to contribute to the health literacy of patients with cancer in relation to early identification, report and self-management of their most common symptoms. As part of the project's objectives, we will aim to show improved self-efficacy (as shown by statistically significantly higher self-efficacy scores) during active chemotherapy for breast cancer, colorectal cancer, or haematological malignancies, and/or at one-year follow-up. It is hoped that an enhanced self-efficacy (evidenced by patients' greater understanding and participation in care, positive attitude, and engagement in seeking health-related information) will in turn enable a smoother rehabilitation process for patients in the post-treatment survivorship period and beyond. EU FP7 Programme Grant agreement No. 602289. Trial registration identifier (clinicaltrials.gov) NCT02356081.